Novel Two-Dimensional Carbon–Chromium Nitride-Based Composite as an Electrocatalyst for Oxygen Reduction Reaction - Khan, Karim; Tareen, Ayesha Khan; Aslam, Muhammad; Khan, Qasim; Khan, Sayed Ali; Khan, Qudrat Ullah; Saleemi, Awais Siddique; Wang, Renheng; Zhang, Yupeng; Guo, Zhongyi; Zhang, Han; Ouyang, Zhengbiao (Frontiers in Chemistry, 2019)
For future pollution free renewable energy production, platinum group metals (PGMs) free electrocatalysts are highly required for oxygen reduction reaction (ORR), to avoid all possible fenton reactions and to make fuel cell more economical. Synthesized porous structure of Cr/rGO nanocomposite without- and with MnO, with estimated surface area of 219 m2g-1 and 379 m2g-1, higher than the carbon black (216 m2.gcat-1) support and almost uniform pore size distribution of about 10 nm and 4 nm, respectively. The Cr/rGO nanocomposite without- and with MnO, exhibit enhanced electrocatalytic ORR properties with high estimated half-wave potential of 0.87 V and 0.9 V versus the reversible hydrogen electrode (RHE) and current density of 5.9 mA.cm-2 and 7.6 mA.cm-2, crossover than that of benchmark 20% Pt/C electrode (0.82 V, 5.4 mA.cm-2), with noticeable methanol-tolerance, and significantly enhanced stability in alkaline media. Hence, the Cr/rGO nanocomposite without- and with MnO, showed superior performance to 20 wt.% Pt/C; the half-wave potential was 50 mV and 80 mV higher, and limiting current density was 0.5 mA.cm-2 2.2 mA.cm-2 higher. In alkaline anion exchange membrane fuel cell (AAEMFC) setup, this cell delivers the power density of 380 mW cm-2 for Cr/rGO nanocomposite with MnO, demonstrating its potential use for energy conversion and storage applications. The nanosize Cr/rGO metallic crystalline nanocomposite without- and with MnO, gives a large active surface area due to the presence of rGO, which also have an effect on the charge distribution and electronic states. Hence, it’s maybe the reason that Cr/rGO nanocomposite without- and with MnO, acts as more active as well as a more stable catalystic material, boosted electrocatalytic properties. The synergistic consequence in nanosized Cr/rGO composites with MnO imparts them overall high electron mobility towards their robust ORR activity in 0.1 M KOH solution. This potential method is highly efficient for synthesis of large scale, nonnoble metal based electrocatalytic (NPMEs) materials, i.e., Cr/rGO nanocomposite without- and with MnO, on gram level and provides efficient approach to prepare novel, lowest cost, highly active, and more stable non-PGM-catalyst for fuel cells.